Dynamic Supply Chains : Delivering value through people - Gattorna, John.; Gattorna, John. (Harlow : Pearson Education, 2010)
J. Sainsbury recently lost share in the market by failing with their supply chain, but Walmart and Dell won by getting their chain right. This work looks beyond the systems and technology and shows how to develop the role of people and behaviour in placing customer-focused supply chains at the heart of your enterprise.
Previous ed.: published as Living supply chains. 2006.
Formerly CIP.
Includes bibliographical references and index.
Keywords: Business logistics